Identification of the factors associated with hirsutism in Lahore - Khan, Khushbakht; Ahmad, Muhammad Riaz; Khan, Mariam (Journal of Pakistan Association of Dermatologists, 2020)
Background Hirsutism is very disturbing condition for most of the women and affects their lives. Hirsute is a medical sign defined as the thick, dark male pattern growth of hair in women. The aim of this study is to explore the factors associated with hirsutism in women of Lahore, Pakistan. Methods This is a case/control study consisted of 300 subjects from whom 150 were cases and 150 controls. Researcher collected data through questionnaires from different beauty parlors, women development centers and Sanatzar institution. Descriptive and inferential analyses were used in order to explain the risk factors associated with hirsutim. To measure the association of hirsute with its risk factors Chi-square, phi and Kendall’s Tau b were used. Odd ratios and 95% confidence intervals computed with the help of logistic regression model. Results Odd ratios and 95% confidence interval for Decrease Breast Size (OR=8.162, C.I=2.797-23.819), Family History of Hirsute (OR=6.980, C.I=3.184-15.299), Acne (OR=2.164, C.I=1.084-4.320) and Polycystic Ovary Syndrome (OR=9.060, C.I=3.492-23.507) were significant. Conclusion There were several risk factors associated with hirsutism, out of these factors decrease breast size, family history, acne and age were most common. Family history and Polycystic Ovary Syndrome (PCOS) were highly associated with hirsute.